IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA HARAPAN (PKH) DI KOTA KUPANG - Amir Syarifudin Kiwang (Journal of Politics and Policy, 2018)
Hope family programs is a program conditional cash assistance to poor families or in international terms known as Conditional Cash Transfers (CCT). Hope family programs intended for help reduce family expenses while increasing investmen for future generations through improving the quality of health and children's education. In the long run, hope family programs expected to break intergenerational poverty chain. As a program Conditional assistance open access to poor families especially pregnant women and children's to utilize various health care facilities and educational service facilities which are available around them. Hope family programs first implemented in 2007 with scattered target in seven provinces namely DKI Jakarta, East Java, West Java, Gorontalo, North Sulawesi , West Sumatera and East Nusa Tenggara (Kupang City). Facts show that Policy Implementation hope family programs has gone well since 2007. In kupang City up to the year 2018 there are around 6.019 heads of family recipient of the family Hope program (latest data 2018, after deducting the participants who leave). Constraints to implementing a family program of hope is a cross-sectoral communication issue and bureaucratic structure in the process of implementing a family program of hope so that it often causes problems in the field. Participants of the Family Hope Program who does not carry out commitments in accordance with verification results will get sanctions in the form of discounted amounts of assistance in the current year.Cooperation between operators and facilitators and all stakeholders be the key to success implementation of the family hope program in kupang city. Keywords : Policy Implementation, Hope family programs.